Aulacoseira konstastinovii sp. nov. and Aulacoseira krylovii sp. nov. – two new centric diatoms from South-east Asia. Issue 4 (1st October 2016) - Glushchenko, Anton; Genkal, Sergey I.; Kulikovskiy, Maxim
Abstract : Two new centric diatom species were found in samples collected from Vietnam and Cambodia, Aulacoseira konstantinovii sp. nov. and Aulacoseira krylovii sp. nov. The former differs from other members of the genus mainly by a characteristic strong undulation in the central area of the valve face. The latter is close to A. konstantinovii sp. nov. but differs in its valve face morphology and having fewer rimoportulae. The new species are illustrated by light microscope and scanning electron microscope images.